4 DEGREE OF FREEDOM ARM ROBOTICS TRAINING FOR STATE VOCATIONAL HIGH SCHOOL 1 DEPOK - Manfaluthy, Mauludi; Widi Dionova, Brainvendra; Desi Hertin, Revita (Community Development Journal, 2024)
This activity provides knowledge about the basics and latest applications in the field of Robotics, especially industrial robots and teaches students to be able to assemble robots. 4 Degree of Freedom Arm Robot is a set of mechanical and electronic tools (mechatronics) that can carry out physical tasks, with 4 degrees of freedom of arm movement robots, namely 1 forward-backward, 2 left-right, 3 up-down. Then there are also three movements at the wrist, namely 4 yaw, 5 pitch and 6 roll. The robot arms have functions to move objects with control using a joystick. With the hope that it can make human work easier in moving objects. To be able to provide students with an understanding of robotics, qualified teachers are needed who have mastered the field of electrical engineering, especially robotics. From the comparison of test results before and after participating in activities by students, a significant increase in knowledge was obtained. Apart from that, students also succeeded in assembling a robot using the materials and components provided.